Penyalahgunaan Keadaan di Perjanjian Pengikatan Jual Beli oleh Developer - Michael Imgran Hetarie (Universitas Batanghari Jambi, 2022)
In the housing loan agreement, the developer provides burdensome conditions for housing consumers. Due to the need for a house, the consumer signs an agreement offered by the developer so that in this case the consumer does not have a position of will and/or bargaining power, no mutually beneficial cooperation. and the consumer does not have the will to make an offer, one party suppresses or takes advantage of the other party as well as the standard clause in the Sale and Purchase Binding Agreement (hereinafter abbreviated as PPJB) between the Developer and the Consumer. This does not cause the content and purpose of the agreement to be prohibited, but causes the abused will not to be given in a free state which is often referred to as state abuse. So that the problem arises what is the concept of abuse of circumstances and what is the legal protection for consumers against abuse of circumstances by developers in the Sale and Purchase Binding Agreement. The problem approach used in this research is the statutory approach, and the conceptual approach. The concept of abuse of circumstances is a concept used to examine the validity of an agreement or contract. The abuse of this situation appears in the agreement that the position of the parties is not balanced with each other so that the parties can impose on other parties whose position is weaker to enter into the agreement. Legal protection for consumers against abuse of circumstances by developers in the Sale and Purchase Binding Agreement is legal protection for consumers against abuse of circumstances by developers in the Sale and Purchase Binding Agreements is the provision of compensation if the fault lies with the business actor as stated in the provisions of article 19 paragraph (1) jo . Article 60 paragraphs (1) and (2) jo. Article 19 paragraph (2) and paragraph (3) of the UUPK relates to a maximum loss of Rp.200,000,000.00 (two hundred million rupiah).